Common pesticides disrupt critical ecological interactions. (March 2023) - Sargent, Risa D.; Carrillo, Juli; Kremen, Claire
Abstract: Critical ecological interactions can be disrupted by pesticides, leading to serious ecosystem and economic harm. For the most part, however, the extent and magnitude of these impacts are unknown. We argue for increased investigation of ecosystem impacts of common pesticides by scientists and scrutiny by regulators.